Penggunaan Media Audio-Visual sebagai Strategi Pembelajaran Inovatif dalam Meningkatkan Kompetensi Sejarah Kebudayaan Islam: The Use of Audio-Visual Media as an Innovative Learning Strategy to Enhance Competence in Islamic Cultural History - Sa'adiyah, Imas (Risalah Kharisma, 2023)
This study examines the effectiveness of audio-visual media as an innovative learning strategy to enhance student competence in Islamic Cultural History (SKI) at MTs Sunanul Huda Cisaat. The research addresses the low student engagement and learning outcomes in SKI due to conventional teaching methods. Using a quasi-experimental design, 48 seventh-grade students were divided into experimental (audio-visual media) and control (conventional method) groups. Data were collected through pre-test and post-test assessments, analyzed using descriptive and inferential statistics (independent sample t-test and N-Gain). Results showed a significant improvement in the experimental group, with an average post-test score of 11.91 (compared to 10.29 in the control group) and an N-Gain of 0.5 (moderate improvement). Statistical analysis confirmed the significant difference (p = 0.001), indicating that audio-visual media effectively enhances learning outcomes. The findings support the integration of multimedia in SKI instruction, aligning with cognitive load theory and dual coding theory, which emphasize multisensory learning. This study recommends adopting audio-visual media to create interactive, engaging, and effective learning experiences in Islamic education.